ANALYSIS OF THE IMPLEMENTATION OF HANDLING PUBLIC COMPLAINTS TO THE PRESIDENT OF THE REPUBLIC OF INDONESIA AT THE MINISTRY OF STATE SECRETARIAT: ANALISIS IMPLEMENTASI PENANGANAN PENGADUAN ‎MASYARAKAT KEPADA PRESIDEN RI PADA KEMENTERIAN ‎SEKRETARIAT NEGARA - Arra Fahamzah; Janiscus Pieter Tanesab (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Public complaints represent a form of public participation in overseeing government ‎administration, and they are mandated to be addressed by government institutions. The ‎Ministry of State Secretariat is one such institution that handles public complaints ‎directed to the President, who is the highest authority in government administration in ‎Indonesia. The implementation of the policy for handling public complaints to the ‎President within the Ministry of State Secretariat presents an interesting locus for ‎research, as it has distinct characteristics compared to other government institutions in ‎managing public complaints. This study uses Grindle's (2017) policy implementation ‎model as the analytical framework, with a post-positivist research approach. The ‎findings indicate that the implementation of public complaint handling to the President ‎by the Ministry of State Secretariat has not been optimal. Although target ‎achievements have been met, they remain inconsistent, and budget allocations are ‎insufficient to support program implementation. In terms of Content of Policy, three ‎aspects are suboptimal: the interests affected, extent of change envision, and the ‎resources used. Regarding Context of Policy, two underperforming aspects are the ‎power, interests, and strategies of the involved actors, as well as implementer ‎compliance. These shortcomings have resulted in a low rate of follow-up responses ‎from relevant institutions to public complaints forwarded by the Ministry of State ‎Secretariat to the President. Additionally, there are still public complaints addressed ‎to the President that are being handled beyond the stipulated time frame.‎